(untitled) (Journal of Asian Development Studies, 2024)
This study scrutinizes the influence of institutional quality, green innovation, foreign direct investment, plus trade openness on green economic growth in emerging Asian countries, with a specific focus on China, India, and Pakistan, covering the period from 1999 to 2023. Using the Autoregressive Distributed Lag (ARDL) model, the research assesses short-run and long-run affiliations among these variables in cooperation. The outcomes illustrate that, in the long run, FDI or green innovation positively contributes to green economic growth, emphasizing their importance in fostering sustainable development. Conversely, institutional quality (IQ) is negatively associated with green growth, suggesting that weak institutional frameworks can hinder environmental progress. TOP also negatively influences green development, likely due to the trade of pollution-intensive goods. In the short run, the effects of FDI are notably adverse. At the same time, the inspiration for green invention, institutional quality, plus trade openness are less significant, implying that their impact on green growth takes more time to manifest. The study finds indications supporting the Environmental Kuznets Curve (EKC) hypothesis for these nations, indicating that conservational degradation initially increases before improving as economic evolution progresses. Partial support is also found for the Pollution Halo Concept, where trade openness and green innovation can lead to cleaner industrial practices over time. Policymakers should focus on improving institutional quality, fostering green FDI, and supporting policies that promote green innovation and sustainable trade practices.